INTRODUCTING PHYSICS EARLY CHILDHOOD CHILDREN USING CREATIVE SCIENCE GAMES IN RA DARRUTAQWA TASIKMALAYA - Abdul Ghofur, Noer Laelly Barorroh Taufik; Sunanih, Sunanih (Indonesian Journal of Early Childhood Education Studies, 2019)
This study aims to improve the science process skills of Early Childhood towards Primary School in RA Daarut Taqwa, Mulyasari Village, Tasikmalaya City, through the application of creative science games (CSG). CSG is a series of interesting games in the form of Apple Spinner and Magic Coin. The method used in this research is the action research method. The action research design of the Kemmis and Mc Taggart model consists of four components which include planning, implementing, observing and reflecting. The results of this study indicate that the application of creative science games can improve science process skills in RA Daarut Taqwa, Mulyasari Village, Tasikmalaya City. Science process skills that emerge and increase are the child's confidence, the process of observing objects / objects or the environment, the process of classifying objects / objects based on color, shape, size or other characteristics, the ability to explore, ask questions, express temporary presumptions, make conclusions , share experiences, and listen to the opinions of others.